Rain garden drainage dynamics modeling by using the Green-Ampt model (Proceedings of Faculty of Civil Engineering, 2024)
The paper presents a relatively simple calculation procedure for modeling the drainage dynamics of rain gardens, i.e. adequately designed infiltration surfaces that are used in urbanized areas for the temporary retention of rainwater. To that end, it is necessary to quantify the infiltration of water into the porous soil, which in general can be very demanding because the hydraulic process in question is described by Richards' partial differential equation, the numerical integration of which is a very challenging task (due to the nonlinearity between the hydraulic conductivity and the degree of saturation determined by its solution). At the same time, relying on several working assumptions stated in the paper, the mathematical description of the subject process can be reduced to the solution of one non-linear algebraic equation, which then creates a relatively simple calculation procedure that can be applied in everyday professional work (if the introduced assumptions can be justified). The calculation procedure is reduced to the integration of Darcy's law, which leads to the Green-Ampt model. The paper presents the argumentation for the aforementioned, calculation procedure intended for practical work, and also offers a numerical example.
Keywords: rain garden; saturation; infiltration; Darcy's law; Green-Ampt model